'Antecedents' and 'postcedents' in relation to satisfaction in Norwegian business relationships. (2015) - Mysen, Tore; Svensson, Göran; Rindell, Anne; Billström, Anders
This study tests whether satisfaction plays an important role as mediator between trust and commitment, and coordination, cooperation and continuity expectance in manufacturer-supplier relationships in Norway. Management in a sample of the 500 largest manufacturer companies was approached by phone to identify key informants and surveys mailed to them. 193 usable questionnaires were received corresponding to a response rate of 38.6%. The results were analysed by structural equation modelling, using SPSS/AMOS 17.0 software. The findings support fairly well the conceptual model tested; trust relates positively to commitment and satisfaction; satisfaction, in turn, relates positively to coordination, cooperation and continuity expectance. However, commitment fails to show any significant relationship with satisfaction. This study makes an important contribution to management and future research about balancing the nomological network of quality constructs in manufacturer-supplier relationships. Results support the major impact trust may have on satisfactory relationships and the importance of satisfaction when establishing well-working governance mechanisms towards gaining enduring relationships.